1993
DOI: 10.2134/agronj1993.00021962008500020011x
|View full text |Cite
|
Sign up to set email alerts
|

Shade Induced Changes in Flower and Pod Number and Flower and Fruit Abscission in Soybean

Abstract: Seed number per unit area is important in determining yield in soybean [Glycine max (L.) Merr.]. Field and greenhouse experiments were conducted to evaluate the role of flowers per plant and flower and fruit abscission in determining pod and seed numbers. Two greenhouse experiments were conducted with the McCall cultivar [Maturity Group (MG) 00] and four cultivars [McCall, Hardin (MG I), Harper (MG III), Essex (MG V)] were used in field experiments in 1989 and 1990. The field experiments used either 0.38‐m (Mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
104
1
9

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 18 publications
9
104
1
9
Order By: Relevance
“…Soybean plants differentiate abundant floral buds, but a large proportion of them abort during development (Kato, 1964;Abernethy et al, 1977): under normal conditions, pod set percentage is only 20 to 40% (Wiebold et al, 1981;Antos and Wiebold, 1984;Jiang and Egli, 1993). By reducing this abortion, it might be possible to increase the pod number, thereby increasing the yield (Kokubun, 2004).…”
mentioning
confidence: 99%
“…Soybean plants differentiate abundant floral buds, but a large proportion of them abort during development (Kato, 1964;Abernethy et al, 1977): under normal conditions, pod set percentage is only 20 to 40% (Wiebold et al, 1981;Antos and Wiebold, 1984;Jiang and Egli, 1993). By reducing this abortion, it might be possible to increase the pod number, thereby increasing the yield (Kokubun, 2004).…”
mentioning
confidence: 99%
“…Under normal growing conditions, pod set percentage ranges from 20 to 40% (Wiebold et al, 1981;Jiang and Egli, 1993). By reducing this abortion, we might be able to increase pod and seed numbers, thereby increasing the yield (Kokubun, 2004).…”
mentioning
confidence: 99%
“…Enhanced the effectiveness of the soybean leaf photosynthesis under light enrichment is resulting in rapid shoot dry matter accumulation. However shading reduced source of leaf canopy photosynthesis, and decreased under-ground plant dry matter weight (Jiang and Egli, 1993).…”
Section: Results and Discussion Shoot Dry Matter Accumulationmentioning
confidence: 96%
“…Mathew et al (2000) analyzed the effects of different light-enriched treatment time on soybean yield components and indicated that there are different responses of seed yield to light enrichment started at late vegetative and early pod formation. However, reducing of light intensity through shade will increase young pods or flowers abscission, lengthen internodes of soybean plant, decrease seed yield and increase plant lodging (Ephrath et al, 1993;Jiang and Egli, 1993;Li et al, 2006). Jiang and Egli (1995) stated that duration of shading also was an important factor influencing soybean yield.…”
Section: Introductionmentioning
confidence: 99%